Intra-abdominal Pressure Has a Good Predictive Power for 28-Day Mortality: A Prospective Observational Study Conducted in Critically Ill Children - Liang, Yujian; Tao, Shaohua; Gu, Bin; Huang, Huimin; Zhong, Zhihai; Shi, Jingrong; Guan, Xiangdong; Tang, Wen (Frontiers in Pediatrics, 2020)
Objective: Elevated intra-abdominal pressure (IAP) is associated with organ dysfunction in critically ill children. Thus far, the predictive value of IAP for mortality remains unknown. Moreover, only few studies determined normal IAP values in pediatric intensive care unit (PICU) children. This study aimed to determine the predictive value of IAP for mortality and calculate normal IAP values in PICU patients. Methods: This prospective observational study was conducted in two PICUs of two tertiary care university teaching hospitals. Patients admitted to the PICU between December 2013 and November 2015 were included. IAP was determined by bladder pressure measurements performed every 8 hours until 48 hours or until PICU discharge. All patients (except neonatal patients) aged ≤14 years who were admitted to the PICUs and had no history of chemical neuromuscular blockade use, neurogenic bladder, or bladder surgery were enrolled. Binary logistic regression was used to analyze the predictive value of IAP for 28-day mortality. Receiver operating characteristic curves were generated to evaluate the prediction effect of IAP. Results: Overall, 229patients were enrolled. IAP (hazard ratio 1.09, 95% confidence interval [CI] 1.029–1.161, P=0.004) and lactic acid (hazard ratio 3.04, 95% CI 1.769–5.21, P<0.001) were independent predictors of 28-day mortality. Additionally, IAP had good predictive power for 28-day mortality, with an area under the curve of 0.74. The optimal cutoff point was 12.13 mmHg (sensitivity 0.58, specificity 0.80).The Youden index was 0.38.Furthermore, 111(48.47%) patients without high-risk factors or clinical manifestations of IAH were analyzed to determine normal IAP values, which were 7.57±2.85 mmHg (range, 1.98–13.16mmHg). There were no significant differences in normal IAP values according to different diseases, sex, age, weight, or body mass index (BMI). Conclusions: IAP has good predictive power for 28-day mortality. The optimal IAP cutoff point is 12.13 mmHg. The IAP reference range is 2.0–13.2 mmHg, which was not associated with factors such as sex, age, weight, and BMI in PICU children. We recommend that IAP be included in critical illness scoring systems in the future.IAP >12.13 mmHg may be more suitable for IAH definition in PICU patients.